2019
DOI: 10.1007/s10461-019-02687-2
|View full text |Cite
|
Sign up to set email alerts
|

From Epidemiology to Action: The Case for Addressing Social Determinants of Health to End HIV in the Southern United States

Abstract: In response to cholera outbreaks in London during 1853-1854, John Snow conducted an historic investigation that launched the field of modern epidemiology [1]. Snow hypothesized that unsanitary conditions caused by sewage dumped into city cesspools contaminated local drinking water, resulting in the rapid spread of Cholera. To test his hypothesis, he collected data from Londoners who acquired and did not acquire cholera, paying close attention to where individuals who contracted cholera lived and acquired their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 59 publications
1
34
0
Order By: Relevance
“…Studies that capture the impact of social determinants of health on viral suppression indicate that factors such as racism, stigma, lack of or poor quality health insurance, and poverty contribute to lower rates of viral suppression [ 22 , 29 , 30 ]. The specific impact of health insurance status on viral suppression is mixed; some studies demonstrate increases in viral suppression rates [ 31 33 ] while others have found no association [ 34 ]. Among persons with a history of IDU social determinants of health have been associated with increased rates of virologic failure [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies that capture the impact of social determinants of health on viral suppression indicate that factors such as racism, stigma, lack of or poor quality health insurance, and poverty contribute to lower rates of viral suppression [ 22 , 29 , 30 ]. The specific impact of health insurance status on viral suppression is mixed; some studies demonstrate increases in viral suppression rates [ 31 33 ] while others have found no association [ 34 ]. Among persons with a history of IDU social determinants of health have been associated with increased rates of virologic failure [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…HIV infection is particularly common in the southern U.S., commonly referred to as the South. The South includes Alabama, Arkansas, Delaware, Florida, Georgia, Kentucky, Louisiana, Maryland, Mississippi, North Carolina, Oklahoma, South Carolina, Tennessee, Texas, Virginia, West Virginia, and Washington, District of Columbia (D.C.) [10][11][12][13][14][15][16][17][18]. In 2017, the South was home to only 38% of the U.S. population [10,16] but had in excess of 50% of the new HIV diagnoses in the country [14,15].…”
Section: Hiv Incidence and Prevalence Rates Among Black Msm In The Southmentioning
confidence: 99%
“…The South includes Alabama, Arkansas, Delaware, Florida, Georgia, Kentucky, Louisiana, Maryland, Mississippi, North Carolina, Oklahoma, South Carolina, Tennessee, Texas, Virginia, West Virginia, and Washington, District of Columbia (D.C.) [10][11][12][13][14][15][16][17][18]. In 2017, the South was home to only 38% of the U.S. population [10,16] but had in excess of 50% of the new HIV diagnoses in the country [14,15]. The nine states commonly and collectively known as the Deep South (Alabama, Florida, Georgia, Louisiana, Mississippi, North Carolina, South Carolina, and Texas) were disproportionately impacted by HIV disease [14,17].…”
Section: Hiv Incidence and Prevalence Rates Among Black Msm In The Southmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiology is the study of the distribution and determinants of disease and other health-related outcomes within populations (4). The application of epidemiology was applied in a disaster setting can produce estimates of the size of affected populations, quantify disaster-related morbidity, mortality and health outcomes (particularly the long-term effects), and provide evidence to demonstrate a causal relationship between exposures and health outcomes (5,6).…”
Section: Introductionmentioning
confidence: 99%